2000
DOI: 10.1021/jo991645o
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Large-Scale Radical Deoxygenation in Alcoholic Solvents Using Sodium Hypophosphite and a Phase-Transfer Agent:  Application to Erythromycins

Abstract: ABT-229 ( 1) is an erythromycin derivative that lacks antibacterial activity but is a potent motilin receptor agonist. 1 As such, 1 is a member of the class of compounds known as motilides, 2 which have been tested in clinical trials as potential prokinetic agents for the treatment of diabetic gastroparesis, gastroesophageal reflux disease, and functional dyspepsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…An immediate problem with NaH 2 PO 2 is its insolubility in most organic solvents. A recent report from the Abbott Laboratories addressed this problem, by describing the use of a phase-transfer agent in alcoholic solvents for the large scale deoxygenation of an erythromycin derivative, and demonstrated the usefulness of NaH 2 PO 2 in radical reductions . However, investigations aimed at the preparation of organophosphorus compounds from hypophosphites under radical conditions have apparently not been conducted since Nifant'ev's studies.…”
Section: Resultsmentioning
confidence: 99%
“…An immediate problem with NaH 2 PO 2 is its insolubility in most organic solvents. A recent report from the Abbott Laboratories addressed this problem, by describing the use of a phase-transfer agent in alcoholic solvents for the large scale deoxygenation of an erythromycin derivative, and demonstrated the usefulness of NaH 2 PO 2 in radical reductions . However, investigations aimed at the preparation of organophosphorus compounds from hypophosphites under radical conditions have apparently not been conducted since Nifant'ev's studies.…”
Section: Resultsmentioning
confidence: 99%
“…108 A similar deoxygenation has also been conducted in alcoholic solvents using NaH 2 PO 2 as the reagent and a water soluble AIBN analogue as initiator (large scale, up to 15 g). 109 The Murphy first showed that hypophosphorous acid salts can also be used as reducing reagents in radical C-C-bond forming reactions. 111 For example, allyl ether 58 was cyclized to benzofuran derivative 59 (Scheme 20).…”
Section: Scheme 18mentioning
confidence: 99%
“…We started our studies with the radical reduction of p -bromobenzyl bromide, using 2,2′-azobis­[2-(2-imidazolin-2-yl)­propane]­dihydrochloride (VA-044) as the radical initiator and sodium hypophosphite monohydrate as the hydrogen atom donor (Scheme a). We thought that using a low-temperature water-soluble initiator and a water-soluble hydrogen atom donor would allow the ability to develop isolation conditions where we could isolate our potential products via a water wash. Upon milling for extended periods of time at 45 °C in the presence of our water-soluble initiator, we observed only unreacted starting materials.…”
Section: Resultsmentioning
confidence: 99%